Anti-inflammatory activities of Italian Chestnut and Eucalyptus honeys on murine RAW 264.7 macrophages. (December 2021) - Cianciosi, Danila; Forbes-Hernandez, Tamara Y.; Alvarez-Suarez, José M.; Ansary, Johura; Quinzi, Denise; Amici, Adolfo; Navarro-Hortal, María D.; Esteban-Muñoz, Adelaida; Quiles, José Luis; Battino, Maurizio; Giampieri, Francesca
Graphical abstract: Highlights: Chestnut and Eucalyptus honeys are rich source of bioactive compounds. They decreased apoptosis in lipopolysaccharide-stressed macrophages. They reduced inflammation and oxidative stress in stressed macrophages. They improved mitochondrial respiration in stressed macrophages. Abstract: The aim of this study was to evaluate for the first time the anti-inflammatory effects of chestnut ( Castanea sativa ) and Eucalyptus ( Eucalyptus occidentalis ) honeys collected in Italy on murine RAW 264.7 macrophages stressed with the bacterial endotoxin lipopolysaccharide (LPS). Pre-treatment with the two honeys markedly decreased apoptosis and stimulated wound healing in macrophages stressed with LPS, where they also reduced the intracellular levels of ROS and nitrite. Additionally, treatment with LPS decreased the levels of glutathione and suppressed the antioxidant enzyme activities, which were significantly ( p < 0.05) increased in the presence of the two honeys, through the modulation of Nrf2 expression; in LPS-stressed macrophages, Chestnut or Eucalyptus honeys protected against inflammation by regulating the main inflammatory biomarkers, including TNF-α, IL-10 and iNOS, through the decrease of NF-кB expression. Finally, they improved mitochondrial respiration and the main related parameters.